Pendampingan Pembelajaran Kosakata Bahasa Arab Melalui Metode Interaktif bagi Anak-Anak di Desa Wanayasa - Lina, Lina; Luthfi, Taufik; Fajar, Ahmad; Munir, Dede Rizal; Raihan, Ulfah (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This study aims to develop an effective method for teaching Arabic vocabulary to children in Wanayasa Village using an interactive approach. The research focuses on the use of media such as songs, flashcards, and educational games to improve students' understanding and interest in learning Arabic. Initial observations revealed that children in Wanayasa Village had limited proficiency in Arabic vocabulary and considered Arabic to be a difficult and boring subject. Therefore, this mentoring program was designed to introduce Arabic vocabulary through engaging activities that encourage active student participation. The results of the study show that the interactive method increased children's involvement in learning, improved their vocabulary comprehension, and changed their perception of Arabic to a more positive one. Evaluations conducted after the mentoring sessions indicate a significant improvement in the mastery of the vocabulary taught. These findings support the theory that varied and enjoyable teaching methods can enhance motivation and learning outcomes, particularly in Arabic language instruction. This study recommends the use of interactive methods as an effective alternative.